MAC Protocols for Optimal Information Retrieval Pattern in Sensor Networks with Mobile Access. Issue 4 (8th September 2005) - Yang, Zhiyu; Dong, Min; Tong, Lang; Sadler, Brian M.
Abstract : In signal field reconstruction applications of sensor network, the locations where the measurements are retrieved from affect the reconstruction performance. In this paper, we consider the design of medium access control (MAC) protocols in sensor networks with mobile access for the desirable information retrieval pattern to minimize the reconstruction distortion. Taking both performance and implementation complexity into consideration, besides the optimal centralized scheduler, we propose three decentralized MAC protocols, namely, decentralized scheduling through carrier sensing, Aloha scheduling, and adaptive Aloha scheduling. Design parameters for the proposed protocols are optimized. Finally, performance comparison among these protocols is provided via simulations.